Prevalência de dor lombar crônica e limitação funcional em profissionais da saúde do setor público em um município da região de fronteira - Reis, Rafael de Souza (2024)
Introduction: Low back pain can be defined as any pain located in the lower region of the spine, with or without pain in the lower limbs, becoming a common health problem worldwide and one of the main causes of disability. Chronic low back pain (CLBP) persists for a period equal to or greater than twelve weeks. In this context, Foz do Iguaçu-PR is characterized as a twin city and serves the Brazilian population residing in Paraguay and Argentina who seek health services. Most healthcare workers are exposed to excessive workloads, high demand for user care, inadequate physical structures, and a shortage of manpower in the sectors. Objective: To identify the prevalence of chronic low back pain and functional limitation in primary and tertiary healthcare professionals, as well as to investigate sociodemographic and occupational variables and measure the intensity and characteristics of pain and determine which region of a border region municipality (Foz do Iguaçu - PR) presents the highest prevalence of healthcare professionals with chronic low back pain in the year 2023. Materials and Methods: This is a quantitative cross-sectional epidemiological study conducted in the city of Foz do Iguaçu-PR in the year 2023. Participants were invited to respond to a questionnaire with sociodemographic and occupational questions, the Roland Morris Questionnaire (RM), and the Graduated Chronic Pain Scale (EGDC-Br). Results: 356 valid questionnaires were completed, of which 16.9% were men and the remainder were women. It was found that Nursing Assistants had a higher BMI than other professionals (p<0.05), with average values of 30.4% ± 5.9 kg/m², classified as OBESITY. The Roland Morris questionnaire showed that 131 (36.8%) healthcare professionals had functional disability, and these same professionals also reported chronic pain of Grade II - low-intensity pain, with 57% of these professionals reporting persistent pain throughout work, as per the EGDC-Br questionnaire. It was evident that the professionals who reported the most disability and chronic low back pain are active in tertiary care (Hospital Padre Germano Lauk), followed by primary care (UBS Jardim América). Conclusion: Public healthcare professionals in Foz do Iguaçu exhibit functional disability and persistent low-intensity chronic low back pain.